On the transformation of some functions of the state in the information society (Journal of actual problems of jurisprudence, 2021)
This article analyzes the modernization of individual functions of the state in the context of digitalization. Based on the analysis of ongoing and planned changes in the public administration system, based on the introduction of modern information technologies, the author concludes that the functions themselves are being improved and transformed. In addition, the author comes to the conclusion that the effectiveness of public administration in modern society is already directly dependent on the use of the latest technologies and procedures. In addition, the state should strive to adapt these procedures and technologies in order to achieve its goals, thereby improving itself. The article analyzes the legislation on digitalization and the changes that were made to it in connection with the updates of public administration processes. The main directions in which digitalization processes are actively implemented, as well as those directions in which this process is to be implemented, are considered. The author conducts a comparative analysis of domestic practice with the practice and legislation of a number of foreign countries. The article focuses on the problems that can be solved by the digitalization process, as well as those issues that do not allow the state to implement Informatization more widely. Key words: public administration, state functions, information society, legal relations, legal consciousness.